The research of plane link complex-structure mechanisms by vector algebra methods - Мацюк, Ирина Николаевна; Шляхов, Эдуард Михайлович (Eastern-European Journal of Enterprise Technologies, 2015)
One of the ways to improve machines is using mechanisms that have enhanced kinematic and dynamic parameters. Complex-structure mechanisms have such characteristics. Their introduction is hampered by a lack of methods for their synthesis and analysis. Analytical investigation of the kinematics of plane eight-link mechanism was performed in the paper. At that, in the kinematic chain there are links that form the slide - block pair. The analytical method of kinematic analysis of plane lever mechanisms of random structure based on the vector representation of links, which allows to use the vector algebra apparatus of the Mathcad package was proposed. Using one-component vectors as unknowns (angular velocities and accelerations) and introducing vector products in equations minimizes the number of equations and the program volume. Research results are presented in a natural form for kinematic parameters, i.e. vector. The considered approach can be used in the analysis and synthesis of complex multilink mechanisms.